Penerapan Strategi Guided Note Taking pada Pembelajaran PKN di Kelas V MI/SD - Olivia Wahyu Ningsih; Rustam Rustam; Abdul Gani Jamora Nasution (Jurnal Pendidikan Dirgantara, 2025)
This research is motivated by the fact that there are differences in the application of the Guided Note Taking (GNT) strategy, Civics teachers only apply two stages of the GNT strategy, namely the opening stage in the form of the teacher rechecking the handout he has made, and the core activity stage in the form of distributing handouts, explaining how to do it, delivering material, and filling in teaching materials (handouts). Civics teachers often do not always carry out the closing stage in the form of reflection and evaluation of learning due to limited time in the learning process. This research methodology uses qualitative research. Data collection techniques were carried out by observation, interviews, and document studies. The results of the study revealed that 1) The opening stage in the GNT strategy carried out in Civics learning in class VB, namely: opening learning with greetings and reading prayers together, checking the readiness of students, making apperceptions, conveying learning objectives, and preparing student record sheets. 2) The core activity stage in the GNT strategy, namely: distributing the note sheet, explaining how to fill in the note sheet, delivering the lesson material, and reading the completed note sheet. 3) The closing stage in the GNT strategy, namely: conducting evaluation, reflecting, giving conclusions, and closing the lesson by reading the prayer after learning together and giving greetings. However, evaluation and reflection activities are not carried out at any time due to time constraints in the learning process.